Managed Devolution sebagai Desain Pengawasan Sistem Merit dalam Perspektif Good Governance - Artika Sari Hassan Yudha Putri (CV Rewang Rencang, 2025)
The merit system is a fundamental principle for promoting professionalism and neutrality among civil servants. However, in Indonesia, its implementation faces structural challenges, especially following the dissolution of KASN as an independent oversight body. This article examines the current gaps in merit system supervision and proposes a managed devolution with central oversight model, inspired by Australia's framework. The study suggests a legal and institutional reform that limits PPK’s discretionary authority and strengthens the role of BKN by establishing an independent merit oversight board to uphold accountability and impartiality in the civil service.